A Study of iPhone’s Attractiveness Factors By the Miryoku Engineering Approach - Lo, C-H; Liao, G-Y; Tang, Z-X; Chen, X-W; Xu, H-F; Hu, J; ., Linda (KnE Social Sciences, 2018)
Since the first iPhone was launched by Apple Inc., more than a decade ago, the iPhone products have remained the attractiveness for consumers in the worldwide market. Except for its unique brand image, excellent marketing strategy, and successful cost control, the superior design of iPhone has been the main contributing factor to its success. The objective of this study is to investigate the attractiveness factors of iPhone. The investigation starts from the product appearance and functions of iPhone. The target products include a range of iPhone products from iPhone 4 to the latest iPhone X, which are analyzed by the evaluation grid method of Miryoku engineering approach and the quantification theory type I. The results indicated that iPhone’s abstract features can generally be classified by the evaluation grid method into (1) Adjectives for appearance: stylish, consistent, high-quality, comfortable, succinct, and proportionally adequate; (2) Adjectives for function: safe, convenient, efficient, and ergonomic. The analysis by the quantification theory type indicated that the male and female preferences are different as follows. For product profile, males pay attention to smooth surface but females prefer matte textures. For product features, males highlight fingerprint recognition but females emphasize more on voice assistant. Design differentiation for different target groups of users is recommended for future smartphones. Follow-up researchers are also advised to carry out investigations on potential users’ gender and experiences of using smartphones of other brands. Keywords: iPhone, smartphone, Miryoku engineering, evaluation grid method, Quantification Theory Type I